Effectivity of Design Thinking Learning on Elementary School Students' Creative Thinking Skills - Juliati; Encep Supriatna; Arie Rakhmat Riyadi (MANDAILING GLOBAL EDUKASIA, 2026)
: Fostering creative thinking skills in early childhood education is paramount to preparing students for 21st-century challenges. However, conventional teacher-centered paradigms frequently stifle student ingenuity, and empirical evidence exploring structured framework interventions such as Design Thinking (DT) in elementary curricula remains scarce. This study aims to examine the influence of design thinking learning on elementary school students' creative thinking skills. Employing a quantitative quasi-experimental approach, this study involved 64 fourth-grade students, systematically assigned to an experimental class (n = 32, utilizing DT pedagogy) and a control class (n = 32, utilizing conventional methods). Data on creative thinking skills were gathered via a validated questionnaire and rigorously analyzed through descriptive analytics alongside paired and independent sample t-tests. The empirical findings demonstrate that DT learning exerts a highly significant positive effect on students' creative thinking. The experimental cohort exhibited a profound shift in mean scores, rising from a pre-treatment baseline of 62.81 (low category) to an impressive 91.68 (very high category) post-treatment. In stark contrast, the control group’s post-test mean stagnated at 64.72 (low category), validating the definitive superiority of the DT framework (p < 0.05). Consequently, DT learning serves as a potent pedagogical alternative to overcome the pervasive deficit in elementary students' creative capacities. Beyond individual performance gains, these results offer crucial insights for educational policymakers and educators to institutionalize human-centered, iterative problem-solving methodologies within primary school curricula.